2019
DOI: 10.1021/acs.orglett.9b01303
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Cobalt Porphyrin-Catalyzed Allylation of Aldehydes with Allyltrimethylsilanes

Abstract: Cationic cobalt porphyrin-catalyzed allylation of aldehydes with allyltrimethylsilanes is developed. The formation of the aldehyde–cobalt porphyrin complex, the key intermediate for the addition of allylsilanes, is confirmed by theoretical studies and synchrotron-based X-ray absorption fine-structure measurements. Facile dissociation of the product by allylation from the cobalt complex regenerates the active complex with the aldehyde. The readily obtainable [Co­(TPP)]­SbF6 complex serves as an efficient cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Peripheral substituents at the meso-and β-positions of the porphyrin complexes substantially modulate their electronic structure. [4][5][6][7][8][9][10][11][12][13][14][15] Modification of the porphyrin skeleton with heteroatoms also changes the electronic properties. [16] 5,15-Diazaporphyrin is a heteroporphyrin that exhibits an electron-accepting nature owing to the iminetype sp 2 -hybridized nitrogen atoms at the meso-positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral substituents at the meso-and β-positions of the porphyrin complexes substantially modulate their electronic structure. [4][5][6][7][8][9][10][11][12][13][14][15] Modification of the porphyrin skeleton with heteroatoms also changes the electronic properties. [16] 5,15-Diazaporphyrin is a heteroporphyrin that exhibits an electron-accepting nature owing to the iminetype sp 2 -hybridized nitrogen atoms at the meso-positions.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins are divalent tetradentate ligands that are able to bind various transition metals. Peripheral substituents at the meso ‐ and β‐positions of the porphyrin complexes substantially modulate their electronic structure [4–15] . Modification of the porphyrin skeleton with heteroatoms also changes the electronic properties [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies were performed to gain some insights into the regiodivergent and stereoselectivity of this strategy. As shown in Figure , four possible intermediates were optimized and calculated by the DFT (B3LYP) method . The results demonstrated that the intermediate of glycal-PdL n -thiophenol (Int.…”
mentioning
confidence: 99%
“…Several effective asymmetric catalytic methodologies with numerous achiral allyl reagents such as allylstannanes, allyl halides, allyl acetates, and allylboronates have been developed. Among them, allylsilanes are broadly used in modern organic synthesis, benefiting from nontoxicity, air and moisture stability, and easy preparation and handling. …”
mentioning
confidence: 99%
“…The asymmetric allylation of aldehydes with allylsilanes, known as the Hosomi–Sakurai reaction, is typically catalyzed by Lewis acids, and notable catalytic asymmetric versions of the reaction have been reported by several research groups . Since the first catalytic asymmetric reaction with chiral (acyloxy)­borane was reported in 1993, titanium- and cerium-based catalysts have provided the corresponding homoallylic alcohols in moderate to good yields with asymmetric induction.…”
mentioning
confidence: 99%